The Innovations of Hibahasan Instrument of Islamic Finance and Islamic Estate Management in Malaysia - Abdul Rahim, Ahmad Khilmy; Abu Bakar, Azizi; Mohd Noor, Mohd Murshidi (Info Sci Publisher, 2021)
The application of hibah as an instrument in estate management is gaining popularity among the Muslim community in Malaysia. “Hibah is a unilateral contract” that elevate welfare and charity. The Islamic financial institutions in Malaysia, including Islamic banks as well as Islamic wealth institutions apply varities of hibah instruments in the products accessible by them. Hibah is a cooperating shariah contract in the Malaysia?s Islamic banking and financial framework. The aim is to incentivize clients for storing their cash into the institution as well as remunerate for clients to pay their financing by agreeing planned. The use of hibah is based on the stated fundamentals and objectives of the “Shariah Advisory Council (SAC) of Bank Negara Malaysia”. Nowadays, hibah instrument has been applied in various forms using Islamic financial institutions especially in Malaysia. This article discusses and analyzes in general the application of contemporary forms of hibah such as Trust Hibah (Hibah Amanah), Conditional Hibah (Hibah Mu'allaqah), Hibah with discussion (Hibah Bi al-Thawab), hibah in saving account (Wadiah) and rental (al-Ijarah) accounts and hibah in Takaful benefit